Nicotine and e-cigarettes addiction - Ahmad Badayai, Abdul Rahman; Wahab, Suzaily; Ahmad Basri, Nadzirah; Essau, Cecilia A. (Academic Press: Elsevier, 2020)
Tobacco use claims more than 8 million lives annually, with most tobacco-related deaths occurring in low and middle-income countries. Second-hand tobacco smoke contributes to an additional 1.2 million deaths annually due to heart disease, cancer, and other diseases. Research appears to show a lack of scientific evidence about the value of e-cigarettes as a smoking cessation tool. Instead, there is evidence of its potential to attract youth to nicotine, acting as a bridge to combustible tobacco use. Smoking initiation during adolescence increases the likelihood of not only being tobacco-dependent but also developing a dependence on other substances in adulthood. The treatment of nicotine addiction in adolescents is similar to the methods used with adults. However, the use of pharmacological treatment in adolescents is still controversial. Among the highly recommended behavioral interventions are cognitive-behavioral strategies, motivational strategies, and social influence strategies.